2020
DOI: 10.1093/icvts/ivaa143
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients diagnosed with COVID-19 in the early postoperative period following cardiac surgery

Abstract: The coronavirus 2019 (COVID-19) pandemic has disrupted patient care across the NHS. Following the suspension of elective surgery, priority was placed in providing urgent and emergency surgery for patients with no alternative treatment. We aim to assess the outcomes of patients undergoing cardiac surgery who have COVID-19 infection diagnosed in the early postoperative period. We identified 9 patients who developed COVID-19 infection following cardiac surgery. These patients had a significant length of hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 5 publications
1
40
1
Order By: Relevance
“…In the subgroup of 51 cardiac surgical patients, the incidence of pulmonary complications was as high as 94.1%, and the mortality was 34% 3 . Yates et al 4 reported similar results: all their patients had pulmonary complications, the postoperative hospital stay was prolonged, and the mortality was 44.4%. Considering all these data, the benign course of the COVID‐19 in our patients might appear paradoxical.…”
Section: Commentmentioning
confidence: 71%
See 1 more Smart Citation
“…In the subgroup of 51 cardiac surgical patients, the incidence of pulmonary complications was as high as 94.1%, and the mortality was 34% 3 . Yates et al 4 reported similar results: all their patients had pulmonary complications, the postoperative hospital stay was prolonged, and the mortality was 44.4%. Considering all these data, the benign course of the COVID‐19 in our patients might appear paradoxical.…”
Section: Commentmentioning
confidence: 71%
“…However, the prevalence of severe comorbid chronic diseases and risk factors was extremely high in our cohort, increasing the theoretic risk of a severe COVID‐19. In fact, data from other series of perioperative COVID‐19 in cardiac surgery showed ubiquitous pulmonary complications and very high mortality rates 3,4 …”
Section: Chance or Causality?mentioning
confidence: 99%
“…[ 14 ] Although there is limited data on the case fatality rate in cardiac surgery patients with COVID-19, the current data suggests elevated mortality, ranging between 16% and 44%. [ 15 , 16 ] Patients undergoing cardiac surgery are becoming medically more complex and have increased cardiovascular risk profiles. Although current risk scores have a high predictive value for perioperative mortality risk in cardiac surgery, [ 17 ] they fail to include the elevated risks of active or previous COVID-19.…”
Section: Preoperative Strategies For Cardiac Surgery Patientsmentioning
confidence: 99%
“…While it is possible that some patients had a false negative result at the time of admission and were in fact already infected at the time of admission, patients who are diagnosed 2 weeks after the hospital admission have definitely contracted the infection in the hospital from other healthcare workers or visitors 2,6 . As a result, a combination of frequent testing of healthcare professionals, not allowing patient visits, double rather than single screening throat swabs, using chest computed tomography in selected cases, broncho‐alveolar lavage for viral testing at the time of intubation in operating theater should be implemented during the pandemic 7 …”
mentioning
confidence: 99%
“…While it is possible that some patients had a false negative result at the time of admission and were in fact already infected at the time of admission, patients who are diagnosed 2 weeks after the hospital admission have definitely contracted the infection in the hospital from other healthcare workers or visitors. 2,6 As a result, a combination of frequent testing of healthcare professionals, not allowing patient visits, double rather than single screening throat swabs, using chest computed tomography in selected cases, broncho-alveolar lavage for viral testing at the time of intubation in operating theater should be implemented during the pandemic. 7 It is currently accepted that COVID-19 infection of cardiac surgical patients is likely to increase the mortality and these patients are classed as moderate to high risk for mortality 5 However, our efforts should be directed to identifying clinical and laboratory markers which may be determinants of adverse outcomes in these patients.…”
mentioning
confidence: 99%